2015
DOI: 10.1002/jsfa.7458
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous decontamination and drying of rough rice using combined pulsed light and holding treatment

Abstract: The obtained results revealed that the combined PL and holding treatment had good potential for successful application in the rice industry to simultaneously achieve disinfection and drying. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The SteriPule‐XL ® 3000 sterilization system (Xenon Corp., Wilmington, MA, USA) was used as the PL generator for conducting this study. A detail schematic diagram of the system was represented in our published paper . The system generated three pulses per second of polychromatic light in the wavelength range of 100–1100 nm at an input voltage of 3800 V. The PL fluence has overlapping AFB 1 and AFB 2 absorbance spectra with the aforementioned wavelengths (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The SteriPule‐XL ® 3000 sterilization system (Xenon Corp., Wilmington, MA, USA) was used as the PL generator for conducting this study. A detail schematic diagram of the system was represented in our published paper . The system generated three pulses per second of polychromatic light in the wavelength range of 100–1100 nm at an input voltage of 3800 V. The PL fluence has overlapping AFB 1 and AFB 2 absorbance spectra with the aforementioned wavelengths (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al . () reported about the suitability of PL in combination with dry heat to disinfect dry rice without adverse effects on milling quality. Aron‐Maftei et al .…”
Section: Pl Treatment Of Other Foodsmentioning
confidence: 99%
“…Some studies were performed in which PL treatments of bulk goods, eggs or cheese surfaces were applied. Wang et al (2015) reported about the suitability of PL in combination with dry heat to disinfect dry rice without adverse effects on milling quality. Aron-Maftei et al (2014a) used PL to inactivate moulds on wheat grain and achieved 3-4 log reduction with only 14-15% loss of the germination power of the wheat seeds.…”
Section: Pl Treatment Of Other Foodsmentioning
confidence: 99%
“…Some species in the genus Aspergillus are widely used in the industrial production of fermented foods, industrial enzyme preparations, and secondary metabolites, such as Aspergillus niger and Aspergillus oryzae . As an environmental factor, light also affects Aspergillus ( 1 7 ). However, at present, research on the light response of fungi mainly focuses on the model species: for example, Aspergillus nidulans and Neurospora crassa ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%